Alasan Islandia Ikut Bergabung Dalam Perjanjian Schengen Pada Tahun 2001 - Wardana, Muh. Husni (2019)
This thesis discusses the reason Iceland joined the Schengen agreement, namely Iceland wants to maintain the Nordic Passport Union which has become a very important collaboration for Nordic countries. The Schengen Agreement contains several policies such as freedom of movement for people, goods, services and investments. This research applies the Organizational Process Model by Graham T.Allison to explain the government units in Iceland which are involved in formulating policies related to Icelandic membership in the Schengen agreement. The Icelandic government units involved in the formulation of the policy are the Prime Minister, Minister of Justice, and Minister of Foreign Affairs The results of this study indicate that Icelandic government units agreed to join the Schengen agreement. This is based on the reason for maintaining the Nordic Passport Union and also not interfering with the sovereignty and constitution of Iceland which is known as an eurosceptic country. Several meetings were held by the Icelandic government during 1996-1999 which later resulted in Iceland officially joining the Schengen agreement in 2001.